Porous Coordination Polymers for Heterogeneous Catalysis - Tang, Fushun; Zhao, John C.-G.; Chen, Banglin (Current Organic Chemistry, 2018)
This short review is aimed at summarizing the most recent developments in using MOFs as the catalysts in heterogeneous catalysis, such as addition and condensation reactions, coupling reactions, cycloaddition reactions, multicomponent reactions, oxidation reactions, reduction of carbon dioxide, enantioselective reactions, hydrogen evolution reactions, polymerization reactions, selective reduction of NOx, and degradation of pollutants.
Keywords: hydrogen evolution